PENGARUH MODEL PEMBELAJARAN COOPERATIVE TIPE JIGSAW TERHADAP KETERAMPILAN BERBICARA PESERTA DIDIK KELAS V SDN 2 WALAHAR : Penelitian Kuantitatif - Dwi Putri, Silvia; Wahyuningsih, Asih; Nurhabibah, Prabawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Based on observations in Grade V at SD Negeri 2 Walahar, the Indonesian language subject particularly speaking skills is considered difficult and less appealing to students. Many students showed a lack of interest in learning, mainly due to the monotonous and less varied teaching methods that failed to stimulate learning motivation. During the learning process, students' active participation was low, and interaction with the teacher was minimal. This condition led to poor learning outcomes, with an average score of only 60, below the Minimum Mastery Criteria (KKTP) of 70. This study aims to determine the differences in learning outcomes before and after the implementation of the cooperative learning model of the jigsaw type and to examine its effect on the speaking skills of Grade V students. The research used a quantitative method with a pre-experimental approach in the form of a one-group pretest-posttest design. The sample consisted of 28 students. The results showed that the average pretest score of 53.57 increased to 81.25 in the posttest. This indicates a significant improvement in speaking skills after applying the jigsaw model. The hypothesis test produced a significance value of 0.000, indicating a significant effect of the jigsaw cooperative learning model on students’ speaking skills. Therefore, it can be concluded that the jigsaw cooperative learning model contributes significantly to improving the speaking skills of Grade V students at SD Negeri 2 Walahar.